2010
DOI: 10.15288/jsad.2010.71.41
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Heavy Episodic Drinking Prevalence and Predictors Among National Samples of American Eighth-and Tenth-Grade Students

Abstract: ABSTRACT. Objective: Given the public health impact of adolescent alcohol use and heavy episodic drinking, we sought to identify the prevalence of types of alcohol use among national samples of 8th-and 10th-grade American students. In addition, a range of known risk factors was used to predict the most problematic type: heavy episodic use. Method: Monitoring the Future data on lifetime, past-year, and past-30-day alcohol use and on past-2-week heavy episodic drinking were available for 505,668 students from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 18 publications
7
90
0
3
Order By: Relevance
“…Generally, youth have their first encounters with alcohol in early or middle adolescence (Patrick and Schulenberg 2010), and the current research demonstrated that parents can have a substantial impact on their children’s alcohol use at this time. Consequently, a well-designed prevention campaign might profitably focus on educating parents about the importance of responsiveness (Donaldson et al 2015) and democratic rule setting (Ennett et al 2013) in addition to the influence of their own drinking behaviors (Van Der Vorst et al 2006) and expectancies (Lamb and Crano 2014).…”
Section: Resultsmentioning
confidence: 72%
“…Generally, youth have their first encounters with alcohol in early or middle adolescence (Patrick and Schulenberg 2010), and the current research demonstrated that parents can have a substantial impact on their children’s alcohol use at this time. Consequently, a well-designed prevention campaign might profitably focus on educating parents about the importance of responsiveness (Donaldson et al 2015) and democratic rule setting (Ennett et al 2013) in addition to the influence of their own drinking behaviors (Van Der Vorst et al 2006) and expectancies (Lamb and Crano 2014).…”
Section: Resultsmentioning
confidence: 72%
“…Interestingly, girls were more likely than boys to use alcohol and marijuana on the weekends. Girls' weekend use likely occurs during unsupervised time with friends (Patrick and Schulenberg, 2010). Particularly, male friends (Velazquez et al, 2011) and dating partners (Collins et al, 2009) represent strong infl uences on girls' substance use (Mrug et al, 2011;Poulin et al, 2011).…”
Section: Gender Differencesmentioning
confidence: 99%
“…Although afternoons are a risky time for younger adolescents, older adolescents engage in greater use in the evenings (Connolly et al, 1992;Sussman et al, 1998). Further, adolescents who spend evenings and weekends with their friends have increased odds of heavy alcohol use (Patrick and Schulenberg, 2010).…”
mentioning
confidence: 99%
“…In the Monitoring the Future Study (Johnston et al, 2008), 39% of eighth graders reported lifetime alcohol use, with 18% drinking to intoxication. Although just 16% consumed alcohol in the past month, 9.5% endorsed heavy episodic use within the past 2 weeks (Johnston et al, 2008), with 61.1% of those having done so more than one time (Patrick and Schulenberg, 2010). Evidence linking age at fi rst use to the development of problematic alcohol use has encouraged research on the emergence of drinking-related behaviors and attitudes in childhood (Dubow et al, 2008;Maggs et al, 2008;Zucker, 2008;Zucker et al, 2009).…”
Section: Abstract: Objectivementioning
confidence: 99%